Pengaruh Pemberian Sekam Padi Bakar Pada Kelembapan Tanah - Tafonao, Agustinus (CV. SINAR HOWUHOWU, 2025)
Soil moisture is a crucial factor affecting plant growth and productivity. One way to enhance the soil's water-holding capacity is through the application of organic materials such as burnt rice husks (biochar). This literature review identifies and analyzes the effects of biochar application on soil moisture. Results show that biochar significantly improves soil moisture by increasing porosity and water retention. It also enhances soil structure and supports microbial activity. However, there are challenges in environmentally friendly production and consistency in quality. Therefore, burnt rice husks can be a sustainable solution for improving soil moisture.